2020
DOI: 10.1186/s12902-020-0499-4
|View full text |Cite
|
Sign up to set email alerts
|

Are there really any predictive factors for a successful weight loss after bariatric surgery?

Abstract: Background: Currently, bariatric surgery is the most effective treatment for severe obesity and its metabolic complications; however, 15-35% of the patients that undergo bariatric surgery do not reach their goal for weight loss. The aim of this study was to determine the proportion of patients that didn't reach the goal of an excess weight loss of 50% or more during the first 12 months and determine the factors associated to this failure. Methods: We obtained the demographic, anthropometric and biochemical inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
85
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(100 citation statements)
references
References 28 publications
9
85
0
6
Order By: Relevance
“…Conversely, other research observed younger age to be more likely associated with WR [82]. As for IWL, older age predicted IWL one year after BS [36]. Likewise, research suggested that male gender was associated with suboptimal or worse WL after RYGB [34,78].…”
Section: Preoperative Predictors Of Wr and Iwl Post-bsmentioning
confidence: 94%
See 3 more Smart Citations
“…Conversely, other research observed younger age to be more likely associated with WR [82]. As for IWL, older age predicted IWL one year after BS [36]. Likewise, research suggested that male gender was associated with suboptimal or worse WL after RYGB [34,78].…”
Section: Preoperative Predictors Of Wr and Iwl Post-bsmentioning
confidence: 94%
“…Interestingly, preoperative psychiatric disorder was a weaker predictor of WR than the postoperative psychiatric disorder, likely due to the impact of the latter on eating behavior after BS [85]. The association of depression and anxiety with IWL has been less examined; however, recent research found that both conditions significantly predicted IWL 1 year after BS [36].…”
Section: Preoperative Predictors Of Wr and Iwl Post-bsmentioning
confidence: 98%
See 2 more Smart Citations
“… 3 We maintain that calculation of %EWL is required to analyze weight-loss success rates. 4 %EWL ≥50 and %TWL ≥25 are commonly used to measure weight-loss success rate. Abandoning use of %EWL may lead to difficulty comparing results with the existing literature.…”
mentioning
confidence: 99%